DEVELOPING MIND MAPPING BASED POCKET BOOK LEARNING MEDIA FOR UNDERSTANDING THE CONCEPT OF INDONESIAN GEOGRAPHIC CONDITIONS MATERIALS AT GRADE V ELEMENTARY SCHOOL - Desi Ayu Pratiwi; Ana Nurhasanah; Zerri Rahman Hakim (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study was a research and development which was based on Borg and Gall model modified by Sugiyono. This model divided the steps of the development process into 6 stages: 1) problem analysis, 2) data collection, 3) product design, 4) validation testing, 5) product revision, and 6) limited testing. This study aimed to produce a product of Mind Mapping-based Pocket Book Learning Media for Understanding the Concept of Indonesian Geographical Materials at grade V. This study also aimed to determine the level of feasibility and understanding of students towards Mind Mapping-based Pocket Book on Indonesian Geographical Conditions. The subjects in this study were 17 fifth grade students of SDN Cimunang Cilik. The analysis technique used in this research was the feasibility analysis technique of expert judgement and students’ understanding tests. The results of this study showed that the results of the assessment by media experts obtained an average percentage of 89.2% with the category "Very Feasible" while the results of the assessment by material experts obtained an average percentage of 91% with the category "Very Feasible", and the results of the assessment by linguists obtained an average percentage of 82.8% in the category of "Very feasible". Finally, the results of the test of students' understanding got an average score of 88.2 in "Good" category. The results of this study indicated that Mind Mapping-based Pocket Book learning media could be used to improve students' understanding on the material of Indonesia's geographical conditions.